The higher nobility in Scotland and their estates, c. 1371-1424 - Grant, A; Alexander Grant (1975)
Few studies relating to the nobility of medieval Scotland have been carried out. Those which have mostly fall into two categories: studies of individual nobles and single noble families, or studies of noble institutions, generally over a long time-scale. With the exception of parts of the work of Professors Ritchie and Barrow on the twelth century, there are no general surveys of the Scottish nobility during a short period. This thesis is an attempt to provide such a survey. It gives an account of the top layer of Scottish noble society in the early Stewart period, that is between 1371 and 1424. A broad view of the nobility, noble estates, and noble institutions has been taken, which is intended to be complementary to other studies of more restricted subjects. The topics dicussed in the thesis have been largely determined by the nature of the sources. The material available for the study of the Scottish nobility in this period consists almost entirely of charters, especially those issued by the crown. Hardly any documents of a more ephemeral nature have survived. In particular (with two slight exceptions) there are none of the account rolls and similar estate records which historians of the English medieval nobility have used to such effect. Because of this, the thesis has a strong topographical and institutional bias. It is possible to say what lands the nobility held and how they held them, but not to describe in any great detail what they did with them, how they were run, or what they were worth.